2024
DOI: 10.7150/thno.88057
|View full text |Cite
|
Sign up to set email alerts
|

ALDH1A1 drives prostate cancer metastases and radioresistance by interplay with AR- and RAR-dependent transcription

Ielizaveta Gorodetska,
Anne Offermann,
Jakob Püschel
et al.

Abstract: Rationale: Current therapies for metastatic osseous disease frequently fail to provide a durable treatment response. To date, there are only limited therapeutic options for metastatic prostate cancer, the mechanisms that drive the survival of metastasis-initiating cells are poorly characterized, and reliable prognostic markers are missing. A high aldehyde dehydrogenase (ALDH) activity has been long considered a marker of cancer stem cells (CSC). Our study characterized a differential role of ALDH1A1 and ALDH1A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 93 publications
0
1
0
1
Order By: Relevance
“…Онкологічне ураження передміхурової залози є другою за поширеністю причиною злоякісних новоутворень у чоловіків, причому метастази в кістки -джерело захворюваності та смертності в запущених випадках [2,3]. Багаторічний досвід підтверджує, що лімфатичні вузли поблизу первинної пухлини є початковими місцями метастазування, за якими йдуть метастази в кістки [4]. Численні дослідження показали, що люди з кістковими метастазами, спричиненими онкологією передміхурової залози, мають гірший прогноз і знижену якість життя [5,6].…”
Section: вступunclassified
“…Онкологічне ураження передміхурової залози є другою за поширеністю причиною злоякісних новоутворень у чоловіків, причому метастази в кістки -джерело захворюваності та смертності в запущених випадках [2,3]. Багаторічний досвід підтверджує, що лімфатичні вузли поблизу первинної пухлини є початковими місцями метастазування, за якими йдуть метастази в кістки [4]. Численні дослідження показали, що люди з кістковими метастазами, спричиненими онкологією передміхурової залози, мають гірший прогноз і знижену якість життя [5,6].…”
Section: вступunclassified
“…An increase in ALDH1A1 in prostate cancer bone metastases was associated with high PLK3 expression. The results demonstrated that ALDH1A1 and PLK3 may serve as biomarkers to predict metastasis and the development of radio-resistance in prostate cancer patients and may represent potential therapeutic targets to eliminate metastatic cells [ 86 ].…”
Section: Targeting Inhibition Of Atra Synthesis To Treat Cancermentioning
confidence: 99%